2019
DOI: 10.4252/wjsc.v11.i12.1130
|View full text |Cite
|
Sign up to set email alerts
|

MiR-301a promotes embryonic stem cell differentiation to cardiomyocytes

Abstract: BACKGROUNDCardiovascular disease is the leading cause of death worldwide. Tissue repair after pathological injury in the heart remains a major challenge due to the limited regenerative ability of cardiomyocytes in adults. Stem cell-derived cardiomyocytes provide a promising source for the cell transplantation-based treatment of injured hearts.AIMTo explore the function and mechanisms of miR-301a in regulating cardiomyocyte differentiation of mouse embryonic stem (mES) cells, and provide experimental evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The inhibition of PTEN at the protein level by miR-301a in vivo was validated in the hearts from AAV9-miR-301a-treated mice ( Figure 6 ). Notably, our recent work also demonstrated downregulation of PTEN by miR-301a in the mouse ESC-differentiated cardiomyocytes 27 .
Figure 5 PTEN is a Target Gene of miR-301a in Cardiomyocytes (A) Comparison between 2,209 predicted target genes of miR-301a in rats, 2,345 predicted target genes of miR-301a in mice, and 487 genes related to heart development.
…”
Section: Resultsmentioning
confidence: 65%
“…The inhibition of PTEN at the protein level by miR-301a in vivo was validated in the hearts from AAV9-miR-301a-treated mice ( Figure 6 ). Notably, our recent work also demonstrated downregulation of PTEN by miR-301a in the mouse ESC-differentiated cardiomyocytes 27 .
Figure 5 PTEN is a Target Gene of miR-301a in Cardiomyocytes (A) Comparison between 2,209 predicted target genes of miR-301a in rats, 2,345 predicted target genes of miR-301a in mice, and 487 genes related to heart development.
…”
Section: Resultsmentioning
confidence: 65%
“…These differentially regulated miRNAs are involved with cation transport, inorganic ion transmembrane transport, regulation of membrane potential, K + ion transmembrane transport and action potential for the up-regulated miRNAs and with heart tube morphogenesis, regulation of cell population proliferation, regulation of cell cycle, angiogenesis, and cell cycle phase transition for the down-regulated miRNAs (Fig. 4h) [76][77][78][79] .…”
Section: Resultsmentioning
confidence: 99%
“…However, insufficient quantity and quality of cardiomyocytes derived from stem cells have become one of the major problems to achieve an effective treatment. Research has shown that the differentiation of stem cells into cardiomyocytes is fundamentally dependent on complex cellular and molecular mechanisms [ 24 , 25 ]. The classical view of gene regulation focuses on protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%